How Local Energy Initiatives Develop Technological Innovations: Growing an Actor Network - Van der Waal, Esther C.; Van der Windt, Henny J.; Van Oost, Ellen C. J. (Sustainability, 2018)
Local energy initiatives are of growing interest to studies of grassroots innovation for sustainability. Some of these initiatives have developed novel technological solutions to fulfil local demand for renewable energy. However, whereas the upscaling and diffusion of grassroots innovations has been extensively discussed in the literature, their emergence has received very little attention so far. We will therefore focus on how energy initiatives can develop technological innovations by bringing together local actors and creating a fit to local circumstances. Grounded in actor network theory (ANT) and structured by concepts from Callon’s sociology of translation, we studied two technologically innovative projects of a Dutch energy initiative. Through document analysis and interviews, we researched how these initiatives developed their innovations by forming networks of social, material, and discursive elements. We found that the outcomes of the innovation processes are very dependent on the networking capacities of the energy initiatives, as well as how well they fit with external circumstances and opportunities. The paper concludes with five lessons for grassroots technological innovation: form links with the local, extensively scrutinize plans, create tangible proof of alignments, position the project as beneficial to as many actors as possible, and adjust the level of ambition to the strength of the actor network.